The health team and the safety of the mother-baby binomial during labor and birth - Dornfeld, Dinara; Rubim Pedro, Eva Neri (Investigación y Educación en Enfermería, 2015)
Goal. Describe the performance of the health care team regarding the safety of both mother and baby during labor and birth. Methodology. Qualitative, descriptive, exploratory study. The subjects were: obstetricians, residents in Obstetrics, pediatricians, nurses, and nursing technicians. The observation technique was used for data collection in a public hospital, between March and July 2010. The data was subjected to thematic content analysis. CEP-GHC (No. 10/001). Results. Data analysis revealed the themes: empathic support, woman’s companion, skin-to-skin contact (SSC), and birth environment. The team promoted safe care through empathic support for women and appreciation and respect for the escort. In relation to SSC and the enabling environment for the reception of the newborn, efforts are still needed for these practices to be configured in secure care circumstances. Conclusion. The Nurse played a differential role in the team for the realization of safe care, because she was predominant in supporting women and promoting CPP. How to cite this article: Dornfeld D, Pedro ENR. The health team and the safety of the mother-baby binomial during labor and birth. Invest Educ Enferm. 2015; 33(1):